Etude du cycle de la reproduction et la fécondité de muge <Liza aurata> (Risso, 1810) (Famille Mugilidae) dans les eaux côtières de Tartous (Syrie) - SAAD, Adib; FINA, Hamoud (INSTM Bulletin : Marine and Freshwater Sciences, 2001)
Biological studies of 852 fishes species liza aurata in Tartous coastal waters showed that it’s reproductive cycle occurs during the period October -November. The first maturity size is about 34 cm (Lt) for females of 3 years age and 30 cm (Lt) for males of 2 years. The absolute fecundity increases with age of fishes.